The history of the development of Keszthely as a holiday resort - Bem, Judit; Kocsis, Tímea; Schaffer, Zsuzsanna (GEORGIKON FOR AGRICULTURE, 2008)
The aim of our essay is to follow up the structural changes of the town of Keszthely from the 1800s to our time. The development of the town was first determined by craftsmen, merchants and the patronizing activities of the Festetics family. During the development of the town it had become a holiday resort by the 20th century as a result of the boom of tourism, and most of the residents lived on activities connected to tourism. In our time an industrial park in the outskirts of a town belongs to its structure, but in Keszthely it has not been established so far. As a result of the declining tendencies of tourism a solution must be found to compensate the loss of income of the residents from tourism so that we can make the town more attractive for industrial businesses.